AN ANALYSIS OF THE TRANSALTION OF ECONOMIC TERMS INTHE BOOK ENTITLED "RICH DAD POOR DAD" BY ROBERT T. KIYOSAKI WITHS SHARON L. LECHTER - Amir Sakib Arsalan, - (2006)
This study entitled An Analysis of the Translation of Economic Terms in the Book Entitled "Rich Dad Poor Dad" by Robert T. Kiyosaki with Sharon L. Lechler'' was aimed at analyzing the translation procedures used in translating economic terms of the book and the quality of translation. ' This study used the descriptive qualitative method by employing the following techniques. First, by reading the original and the translated book versions Rich Dad Poor Dad to obtain the data of economic terms used in the book and how they were translated. Second, by asking them to read the book. Third, by distributing the questionnaires to five reviewers in order to answer the second question of the research questions. The data were analyzed and interpreted by using descriptive explanation. The researcher found out that the naturalization was the most frequent procedure used by the translator in translating economic terms in the book. However, there were also the other kinds of translation procedure used in the book: literal, couplets, equivalent, expansion, transposition, paraphrase, synonymy, through, and transference. Based on the reviewers' judgments, the quality of the translated book was relatively good because they can understand the message of thebook and the naturalization was the most frequent procedure used by the translator. Consequently, the translated version published by Gramedia is interesting to the readers.